Knowledge based economy and knowledge society : some starting points - Švarc, Jadranka; Lažnjak, Jasminka (2004)
In the text is given the overview of the knowledge based society/economy theories compared with triple helix theory and national innovation system as basis for new science and technology policy in transition countries.
Projekt MZOS
ENG